Ironclad = [videorecording (DVD)] Assiégés - English, Jonathan; Purefoy, James, 1964-; Jacobi, Derek; Mara, Kate, 1983-; Giamatti, Paul (Distributed exclusively in Canada by Alliance Films, 2011)
"It is the year 1215 and England is on the brink of a bloody Civil War. The Magna Carta, a landmark contract between the King and his subjects, upholds the rights of the people of England and promises to bestow a fragile peace on the kingdom. Yet, barely four months since putting his royal seal to the charter, the sly and deceitful King John (PAUL GIAMATTI) amasses a powerful mercenary army and plans to destroy all those who signed the legendary charter, in order to once again seize absolute control of the country. Hearing news of their despised ruler's intentions, a Templar Knight (JAMES PUREFOY), hastily assembles a band of noble barons prepared to hole up inside the virtually impenetrable walls of Rochester Castle in order to protect the people's rights. There they must rely on their superior swordsmanship and sheer determination to defend their freedom, defeat the forces of an oppressive King and bring justice to the people of England."--Container.